NEW DAWN OR ETERNAL TWILIGHT? - Shubin, Vladimir (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article was prepared within the project "Post-crisis world order: challenges and technologies, competition and cooperation" supported by the grant from Ministry of Science and Higher Education of the Russian Federation program for research projects in priority areas of scientific and technological development (Agreement № 075-15-2020-783).